Estruturas autoconstruídas de tionina sobre grafeno: formação, organização e dopagem - Thiago Alonso Stephan Lacerda de Sousa (2019)
The association of organic molecules with 2D materials constitutes an important testbed for both the basic science of self-assembly and its perspective applications. Following this concept, this thesis describes a rich phenomenology that is involved in the interaction of thionine with graphene, leading to a hybrid material by well-organized self-assembled structures atop graphene. This composite system is investigated by atomic force microscopy (AFM), electric transport measurements, Raman spectroscopy and density functional theory (DFT) calculations. Results show an interesting time evolution of thionine self-assembled structures atop graphene, forming either monolayer islands or well-organized bilayer filaments. Moreover, the final molecular assembly is highly oriented and follows specific crystallographic directions in graphene. A strong n-type doping effect in graphene, which allows the graphene functionalization with thionine to be used as a tool to design novel nanoelectronic devices through selective doping control, is also observed. In order to compare the influence of the substrate polarity in the conformation of thionine molecules, additional experiments using mica as a hydrophilic substrate are carried out, since graphene is a hydrophobic substrate. The conformation of thionine molecules over the hydrophilic substrate and over the hydrophobic substrate shows opposite trends: thionine molecules lay parallel to mica surface, while they lay perpendicular to graphene surface. Therefore, the present results may pave the way for future applications of thionine molecules in the construction of graphene-based nanodevices upon properly chosen molecular self-assembly processes.